Asymptomatic left ventricular diastolic dysfunction in NIDDM; evaluation and association with glycemic control - Muhammad Kashif; Yasir, Ali; Hakim, Amber; Abdur Rasheed (International Journal of Endorsing Health Science Research, 2016)
DM is an established risk factor for congestive cardiac failure, in which the diastolic function is impaired. The majority of these patients may be asymptomatic without signs of overt heart failure. The aim of this study was to determine asymptomatic Left Ventricular Diastolic Dysfuction (LVDD) in Non-Insulin Dependent Diabetes Mellitus (NIDDM) in association with glycemic control and to assess the risk factors for the development of diastolic dysfunction. This cross sectional study was conducted at the Tabba Heart Institute, Karachi from Dec, 2011 to Nov 2012, 101 asymptomatic patients with type 2 diabetes without evidence of cardio-respiratory illness were enrolled. LVDD was evaluated by Doppler echocardiography, which included the valsalva manoeuvre. A total of 101 patients, LVDD was found in 67 subjects (66.34%) of whom 52 (51.48%) had impaired relaxation and 15 (14.85%) had a pseudonormal pattern of ventricular filling. The potential risk factors for the development of LVDD in type 2 diabetics were (a) age ≥45 years was associated with an almost three times higher risk for LVDD, (b) females had almost two times a higher risk of LVDD as compared with men, and (c) Diabetic patients of more than two years’ duration had a two times higher risk of LVDD. The study results also indicate that LVDD was significantly associated with increased age, longer duration of Diabetes and glycemic control (glycated HbA1c levels) and LVDD is found in diabetic patients before the onset of clinically detectable disease. The high prevalence of LVDD suggests that screening for LVDD should include procedures such as the valsalva manoeuvre.